Konsep Mendidik Anak di Era Modern dalam Perspektif Hadis: Studi Syarah dan Takhrij Hadis - Imam Musyaffa; Fitriani Fitriani (Gunung Djati Conference Series, 2022)
This study aims to discuss hadith about the concept of educating children in the modern era. This research uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about the concept of educating children in the modern era based on the hadith narrated by Imam Muslim No. 3084. The results and discussion of this study indicate that the status of the hadith is of sahih quality that meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the Hadith narrated by Muslim No. 3084 is relevant to be used as a motivation to develop oneself into a successful parent in educating children.